Variaciones del fitoplancton en cuatro lagunas costeras del Estado de Yucatán, México - Herrera-Silveira, Jorge A. (1999)
The Yucatan State, SE Mexico, shows unique geohydrological conditions which favoured the presence of coastal lagoons with different salinity gradients. Celestun lagoon shows an oligohaline-marine pattern (10-38psu), in Chelem lagoon the salinity is marine-hiperhaline (32-48psu), while Dzilam is polihaline-marine (20-36psu), and Rio Lagartos is polihaline-hiperhaline (28-120psu). The objective of this study was identify the space and seasonal changes of the dominants groups of phytoplankton in these lagoons, and relate them to hydrological characteristics. At this time, 466 taxa hare been recognized for the four lagoons. Celestun is dominated by Bacillariorhyta and Pyrrophyla, in Chelem and Dzilam the dominant group is Bacillariophyta, while in Rio Lagartos is Cyanobacteria, suggesting that differences among lagoons are related to the water exchange between the lagoon and sea, and the groundwater discharges as the dominant factors.